Kebutuhan afiliasi dan perilaku seksual pada mahasiswa - Alifia Satyana (Fakultas Psikologi, 2020)
ABSTRACT College students are in early adulthood developmental phase, which individuals usually try to gain closeness by establishing committed relationship to other individuals such as dating. It supposed to lead to premarital sexual behavior. In dating relationships someone usually do direct contact with his/her partner. These behaviors done to meet the need for attention, support and affection called the needs of affiliation. The purpose of this study was to determine the correlation between the needs of affiliation and premarital sexual behavior in college students. Research subjects were 150 college students who are dating, collected by quota sampling technique, and analyzed by Pearson's product moment correlation method. The results showed correlation coefficient (r) of 0.180 and significant value of 0.014 < 0.05, means that there is positive significant correlation between the needs of affiliation and premarital sexual behavior in students who are dating.